Bridging iron biofortification through integrative strategies from QTL mapping to regulatory-compliant genome editing - Sadia Hakeem; Safia Khushi; Muhammad Hammad Nadeem Tahir; Nadia Hussain Ahmed; Amna Bibi; Zulfiqar Ali (Cereal Research Communications, 2026)
Around two billion people are affected by iron (Fe) malnutrition globally, largely contributed by the consumption of cereal-based diets with low levels of iron and reduced bioavailability due to presence of inhibitor compounds like phenols and phytic acid. Among several methods of enhancing Fe content of staples, genetic biofortification is the most sustainable, and cost-effective method. Genetic biofortification through conventional breeding has succeeded in producing a number of cultivars marketed for high nutrition. However, this approach is limited due to the requirement of large genetic variation, long breeding time, phyto-availability of nutrients through soil only, gene targeting in compatible species only, lack of knowledge of QTL and genetic maps, environmental interactions, risk of linkage drag, and complex interrelations among nutrients as well as with other yield traits. With the advent of genomic approaches for targeted genetic manipulation, transgenic approach offers straightforward and robust techniques to genetically biofortify staples. While transgenic approaches to increasing Fe content have been helpful, genetically modified (GM) cultivars for staple crops may be delayed due to GM regulatory barriers. This chapter reviews the global status of Fe malnutrition, possible solutions to combat its deficiency, and bottlenecks towards Fe biofortification in staples. It also provides insights into transgenic approaches to address this issue as well as way forward to resolve the regulatory issues associated with GM crops by providing alternate options.